Framing Ageing as a Medical Problem: Public Discourses on Older Adults, Health Risks and Tecnoscientific Solutions in the UK and Italy - Francesco Miele; Federico Neresini; Emanuele Di Buccio (Tecnoscienza)
This work aims at contributing to the debate around the social representations of ageing, here by considering the theory of “biomedicalisation of ageing”, for which getting older is transformed into a medical problem with specific health risks that can be treated thanks to the help of technoscientific innovations. A considerable body of literature has created and developed this theoretical perspective, mainly through conceptual contributions or with qualitative methods, but different from most research, our paper contains a comparative-quantitative analysis of two large datasets, consisting of all the articles regarding the older population published online on the Guardian (UK) and la Repubblica (Italy). These articles underwent a quantitative analysis based on topic modelling techniques to identify and analyse the relevant topics. In parallel, we developed some synthetic indices to support the analysis of how news about older people is “biomedicalised” in media coverage. First, our analyses show how, during the period under scrutiny (1985-2021), while older adults have been increasingly framed as subjects at risk, the technoscientific solutions typical of the biomedicalisation era (i.e., personalised medicine and devices for self-monitoring vital parameters as well as lifestyles) have become increasingly relevant in the media sphere. Second, the analysed data show how biomedicalisation processes are interwoven with the ongoing social, cultural and economic arrangements (e.g., reduction in welfare state spending and exacerbation of the ageing population). Finally, focusing on the 2020-2021 period, it is observable how during COVID-19 public attention to the health risks of older adults has further increased; at the same time, there has been a diminishing emphasis on technoscientific solutions within the public sphere.